The re-organization of action in golf putting under different taskconstraints - Vaz, Vasco (2022)
Background: The behaviours of golfers could be interpreted as emergent, resulting from the cyclical relations of perception-action couplings established under the interacting constraints of competitive performance environments. Underpinned by an ecological dynamics approach, the aim of this study was to investigate how a simple adaptation of task constraints constrained the (re)organization of putting actions in skilled golfers. Methods: Ten skilled golfers, male and right-handed (42.6 14.4 years old) (average handicap of 2.3 1.7) were investigated when putting at different distances from the hole. Results: Our results have revealed how the coupling of perception and action captures the mutual relationship that emerges between a performance environment and each golfer’s abilities, during task performance. In this sense, the manipulation of distance constraints selectively constrained movement organization variables in specific ways. As distance to the hole increased, there was a clear increment in backswing, downswing and follow-through amplitude, speed of putter impact on the ball and maximum acceleration of the putting movement. Moreover, heart rate (HR) decreased with distance to the hole, which may have indicated that a golfer was adapting to increasing distance constraints, or that a greater distance from the hole may require a greater attentional focus. Conclusions: Underpinned by an ecological dynamics approach, these and other findings in our study suggested some regularities in the behaviour of golfers when environmental constraints (e.g., distance) are manipulated. Thus, golfers’ behaviours can be interpreted as an emergent process resulting from the perception-action coupling relations established during practice and performance.